A novel method oriented to evaluate the real characteristics of practical buck zero-voltage switching quasi-resonant converters. - Polyzos, N.P (IEEE Transactions on power electronics)
The output characteristics of buck zero-voltage switching quasi-resonant converters (ZVS-QRCs), presented in previously published works, are calculated considering equal input and output energies. Nevertheless, measurements that were taken with breadboarded buck ZVS-QRCs demonstrate an important deviation between the results of the theoretical analysis and the experimental data. This deviation becomes greater when the load current increases. This paper deals with a novel simulation method to approximate the real behavioral characteristics of Buck ZVS-QRCs. Analytical expressions are derived to calculate the power losses in each power converter component as well as the DC-voltage conversion ratio. Computer simulation results are confronted to experimental ones proving the effectiveness of the proposed method